INSTRUIRE PENTRU INOVAŢIE LA BIBLIOTECA MUNICIPALĂ „B.P. HASDEU” - KULIKOVSKI,Conf. univ. dr., Departamentul comunicare şi teoria informării, Universitatea de Stat din Moldova, Lidia (BIBLIOPOLIS, 2020)
In order to promote the innovation, at the Municipal library "B.P. Hasdeu" was held some trainings FedEx Days @ Hasdeu. The activity is a non-formal learning method, which is destinated to collect, to develop and to promote employees’ ideas. Motivating employees to generate ideas is part of the key components, and it's also an element of motivation 3.0. Invented in 2002 in Australia, the training for innovation is spreading around the world, reaching the Republic of Moldova.